Postgraduate EFL Students’ Response t o Feedback: What Feedback Do Students Prefer? - SITI ZULAIHA; AKHMAD HAQIQI MA'MUN; HERRI MULYONO (Indonesian Research Journal in Education |IRJE|, 2020)
The present study aimed at investigating postgraduate EFL students’ preferences for feedback and reasons behind their preferences. This study employed a qualitative research design with a case study approach. Students at an English study program participated in an in-depth interview. Data were analyzed using a qualitative content analysis. Findings revealed that the majority of postgraduate EFL students in this study preferred written, specific, detailed, regular, constructive, and timely feedback. Students showed interest in the feedback they received and desired to discuss with their lecturers about the feedback. The findings emphasize the need for dialogic feedback where students and lecturers can share an understanding of what feedback is and improve the way the feedback process is done. Suggestions, implications, and limitations are also discussed.